If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 4 + 3x = 12 Reorder the terms: 4 + x + 3x = 12 Combine like terms: x + 3x = 4x 4 + 4x = 12 Solving 4 + 4x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 4x = 12 + -4 Combine like terms: 4 + -4 = 0 0 + 4x = 12 + -4 4x = 12 + -4 Combine like terms: 12 + -4 = 8 4x = 8 Divide each side by '4'. x = 2 Simplifying x = 2
| 2y+6=y+10 | | y^2-9y=-14 | | 2n-7+3n=18 | | 2x+6+6x=86 | | t^2-2t=20 | | 27x^2-18x+3=0 | | 10x^2+72x-64=0 | | 102-(4x+15)=4(x+6)+x | | y^2(y-4)=5y-14 | | 48-16= | | x^2+6x+13=x+5 | | 18-2g=4 | | S=-16t^2+48t | | 5x+93y=5 | | 5y+2=2(y-4) | | p(x)=x^3-x^2-4x-6 | | -(x-1)=4x-14 | | (3x^2+5x+2)+(8x^2-6)= | | 81-2x=25x+15 | | -5x+21=-7x+26 | | 2x+9=45-7x | | 9(4x+3)-2(2x-2)=-4 | | 2x^2-75=175 | | -3(m+2)+m=-22 | | 23b+(-19b)-1=31 | | (x^3+y^3)+13(-12xy)= | | (x^3+y^3)+13-(12xy)= | | (x^3+y^3)+13-12xy= | | 5(a-11)=-35 | | (x^3+y^3)-12xy+13= | | x^3+y^3-12xy+13= | | 8=5-c |